Implementationof Religious Guidances in Patients Care Unit III IbnuSina Hospital YW-UMI Makassar - Nur Setiawati; Bisyri Abdul Karim (RedwhitePress)
Spiritual guidance for hospital patients is increasingly recognized as having an effective role and benefits for healing patients. Therefore, this study will reveal the implementation of religious guidance in patient unit care III at IbnuSina Hospital, Indonesian Muslim University (UMI) in Makassar. This study aims to identify the forms of religious services applied by the IbnSina UMI Makassar hospital and to know the influence and benefits of religious services felt by patients. This type of research is a mixed method between qualitative and quantitative. Data collection is done through library search, observation, interviews, filling out questionnaires, and documentation. The results showed that the impelementation of religious guidance applied in IbnSina UMI Makassar hospital had a positive change of 69% of patients who were more enthusiastic in living, more motivated to recover, more calm, positive thinking, and more diligent in worshiping. The results of this study are very important and useful for the development of spiritual services in other various hospitals.